Moving away from lexicalism in psycho- and neuro-linguistics - Krauska, Alexandra; Lau, Ellen (Frontiers in Language Sciences, 2023)
In standard models of language production or comprehension, the elements which are retrieved from memory and combined into a syntactic structure are ‘lemmas’ or ‘lexical items’. Such models implicitly take a ‘lexicalist’ approach, which assumes that lexical items store meaning, syntax, and form together, that syntactic and lexical processes are distinct, and that syntactic structure does not extend below the word level. Across the last several decades, linguistic research examining a typologically diverse set of languages has provided strong evidence against this approach. These findings suggest that syntactic processes apply both above and below the word level, and that both meaning and form are partially determined by the syntactic context, not just by the words themselves. This has significant implications for psychological and neurological models of language processing as well as for the way that we understand different types of aphasia and other language disorders. As a consequence of the lexicalist assumptions of these models, there are many kinds of sentences that speakers produce and comprehend - in a variety of languages, including English - which are challenging for them to account for. Here we focus on language production as a case study. In order to move away from lexicalism in psycho- and neuro-linguistics, it is not enough to simply update the syntactic representations of words or phrases; the processing algorithms involved in language production are constrained by the lexicalist representations that they operate on, and thus also need to be reimagined. We provide an overview of the arguments against lexicalism, discuss how lexicalist assumptions are represented in models of language production, and examine the types of phenomena that they struggle to account for as a consequence. We also outline what a non-lexicalist alternative might look like, as a model that does not rely on a lemma representation, but instead represents that knowledge as mappings between (a) meaning and syntax, and (b) syntax and form, with a single integrated stage for the retrieval and assembly of syntactic structure. By moving away from lexicalist assumptions, this kind of model provides better cross-linguistic coverage and aligns better with contemporary syntactic theory.